Social capital in agricultural irrigation management of “RBUMDES Mursapa” - Rustinsyah Rustinsyah (Faculty of Social and Political Science, Universitas Airlangga, 2019)
Peasants in Plandirejo Village who live along the Bengawan Solo River use river water for agriculture. To distribute river water to agricultural land use the pump. It needs to be managed together so that it can be used properly. RBUMDES Mursapa as an institution that has succeeded in managing agriculture in Plandirejo Village. The role of social capital as one of the factors causing success in managing agriculture. Social capital is a network of elements of stakeholders involved in achieving the same goals. Therefore, qualitative research was conducted from June 2016 to July 2017 by collecting data through observation, interviews and FGD (Focus Discussion Group) with stakeholders managing agriculture. The purpose of the study is to describe social capital in irrigation management and its consideration of the sustainability of agricultural activities in the village. The results of this study are: a) social capital has an important role to succeed in managing agriculture; and b) agricultural development planning between the sustainability of agriculture and the development of communities in the village such as agricultural production which is quite high, in the agricultural and non-agricultural sectors, and provides support for national agricultural improvement programs. The impacts of the success of RBUMDES Mursapa include: a) contributes to rural development and accommodates the activities of village government; b) to mobilize rural farming activities; c) open up employment for male and female.